SISTEM INFORMASI PEMASARAN PRODUK USAHA KECIL DAN MENENGAH (UKM) KOTA PALEMBANG - Ahmad Haidar Mirza; Ade Putra; Hasmawaty _ (IST AKPRIND Yogyakarta, 2018)
Rapid Application Development (RAD) is a method of developing user interfaces that prioritize activities in analyzing data, designing and building an information system. In the Marketing Information System research, the Small and Medium Enterprises (SMEs) products in Palembang City are in desperate need of a process of data analysis that needed by SMEs in Palembang in marketing their products. In this Information System is also equipped with transaction and chat features so that consumers who are interested in SMEs products can directly make purchase transactions directly with producers of the product, with this Information System expected the marketing process in distributing and introducing products that have been produced by SMEs in Palembang City is able to reach consumers outside the city of Palembang and is able to improve the standard of living of SMEs in the city of Palembang, because SMEs are one of the economic sectors that provide considerable contribution to the growth of micro-economies both regionally and nationally